ASSY-I Screening: A Suicidality Scale for Argentinean Young Students - Galarza, Aixa; Fernández Liporace, Mercedes; Castañeiras, Claudia; Freiberg-Hoffmann, Agustín (Psykhe, 2023)
This study aimed at deepening into the internal structure's analysis of the Argentinean Scale of Suicidality, Youth version—ASSY-I Screening—. The 6-factor model obtained in a previous exploratory factor study was tested via confirmatory factor analysis, and further compared with an alternative second-order model. The factorial invariance was examined using the self-perceived gender as a splitting variable. The factors' internal consistency was analysed in the whole sample and in two subsamples comprising exclusively men and women. The scores' stability-reliability was examined using a test-retest analysis. The sample was composed of 632 students with ages between 13 and 21 years old (M = 17.88, SD = 2.16; 64.08% women, 35.92% men). Results showed evidence favouring the robustness of the ASSY-I model as well as the likelihood of generalising it across groups in the local population of young students. Findings are discussed regarding further uses of the scale in the professional field.